DIRECTIONS OF DIVERSIFICATION OF THE STRUCTURE OF THE NATIONAL ECONOMY - Ramazonova Zarnigor Avazovna (Web of Journals Publishing, 2024)
In this article, I have presented the results of international theory and practice in the directions of diversification of the structure of the national economy, as well as the application and forecasts of practical work in the Republic of Uzbekistan.
Keywords: Diversification, Garri Markovitz, Maykl Gort, economic diversification index, strategy of diversification, UNIDO.